Faktor Determinan Jiwa Wirausaha Pedagang Minangkabau Perantauan: Determinant Factors of Entrepreneurial Spirits among the Minangkabau Migrant Merchants - Hendra Cipta (Society, 2019)
This research aims to reveal the dominant factors of Minangkabau (the ethnic group native to the highlands of West Sumatra, Indonesia) migrants mainly engaged in merchandise. The Minangkabau hold firmly their customs and traditions which founded upon Islamic law as described in the saying “adat basandi syara’; syara’ basandi kitabullah” (tradition founded upon Islamic law, Islamic law founded upon the Holy Quran). This research was conducted in Ipuh sub-sub-district, Bengkulu province, Indonesia, those 150 respondents of Minangkabau merchants as the samples. The location was selected due to Ipuh sub-district is located near West Sumatra borders, so that the tradition strongly influence the Minang migrant merchants. To answer the research questions, the variables used were independent and dependent. The independent variable is the entrepreneurial spirit, while, the dependent variable is economic factors, adat (in this case, the term used is tradition), descendant, education, and independence. The research used a quantitative method by using multiple linear regressions. The result found that cultural variables influence the entrepreneurial spirits of Minangkabau merchant migrants because they uphold their traditions wherever they are. The insignificant influence of education, economic factor, heredity, and independence are insignificant. To conclude, matrilineal tradition has influenced the entrepreneurial spirits of Minang merchants and the matrilineal tradition can increase entrepreneurs among women.